1997
DOI: 10.1095/biolreprod56.3.608
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Long-Term Bovine Granulosa Cell Culture System: Induction and Maintenance of Estradiol Production, Response to Follicle-Stimulating Hormone, and Morphological Characteristics1

Abstract: The objectives of this study were to develop a serum-free bovine granulosa cell culture system in which FSH-responsive estradiol production could be induced and maintained, and to use this system to evaluate the effects of FSH, insulin, and IGF-I on steroidogenesis and proliferation of bovine granulosa cells from different follicle size categories (< 4-, 4-8, and > 8-mm diameter). In the presence of FSH, granulosa cells from small follicles differentiated in vitro, and estradiol secretion increased with time (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
233
6
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(282 citation statements)
references
References 46 publications
33
233
6
5
Order By: Relevance
“…Lipoproteins, especially LDL and HDL, which are rich in methionine and lysine (Auboiron et al, 1995), are essential for the transport of cholesterol, which is the precursor of biosynthesis of steroid hormones such as estrogens and progesterone (Hall, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoproteins, especially LDL and HDL, which are rich in methionine and lysine (Auboiron et al, 1995), are essential for the transport of cholesterol, which is the precursor of biosynthesis of steroid hormones such as estrogens and progesterone (Hall, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the higher intake of energy by ewes under overfeeding possibly caused increase in the blood glucose, insulin and IGF-I concentration. Insulin directly stimulates both mitosis and production of steroids in granulosa (Gutierrez et al, 1997) and theca (Stewart et al, 1995) cells, and IGF-I increases the sensitivity of cells to FSH (Adashi et al, 1985), promoting follicular development (Webb et al, 2004). Overfeeding can also increase the number of ovulations for resulting in higher hepatic metabolization of steroid hormones, consequently, decreasing the negative feedback of such hormones on the release of gonadotropins FSH and LH (Smith & Stewart, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…However, in cultured bovine granulosa cells harvested from small bovine antral follicles, the addition of low dose of FSH maintains follicle characteristics by stimulating E 2 and CYP19A1 for several days (Gutierrez et al 1997, Silva & Price 2002, Sahmi et al 2004) and appears to counteract the process of luteinization by inhibiting STAR mRNA expression (Zheng et al 2008). Our previous study showed that TGFB1 inhibits stimulation of E 2 and P 4 synthesis in bovine granulosa cells cultured in the presence of FSH (Zheng et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture was performed essentially as described by Gutierrez et al (1997). Briefly, ovaries were collected at a local abattoir from adult cows irrespective of stage of the estrous cycle and transported to the laboratory at 37 8C in PBS containing penicillin (100 U/ml), streptomycin (100 mg/ml), and fungizone (1 mg/ml).…”
Section: Cell Culturementioning
confidence: 99%
“…Insulin can enhance FSH-stimulated oestradiol production in bovine granulosa cells (Spicer et al 1993, Gong et al 1994, Gutiérrez et al 1997, and can induce Cyp19 expression and/or oestradiol secretion in bovine granulosa cells in the absence of FSH (Gutiérrez et al 1997, Silva & Price 2000. Insulin binds to its receptor, which induces autophosphorylation of the receptor b-subunit, which in turn phosphorylates insulin receptor substrate-1 (IRS-1; Poretsky et al 1999).…”
Section: Introductionmentioning
confidence: 99%